2013
DOI: 10.1068/i0601jw
|View full text |Cite
|
Sign up to set email alerts
|

Implicit Association of Symmetry with Positive Valence, High Arousal and Simplicity

Abstract: Abstract. Symmetrical visual patterns are preferred to random patterns. Studies using the Implicit Association Test (IAT) have shown that symmetry is associated with positive valence words (e.g. love), and random with negative valence words (e.g. hate). Valence is an important aspect of emotion, but equally interesting is the relationship between the symmetry-random dimension and the dimensions of arousal and complexity. Possible links have long been discussed but empirical evidence is limited. Using a series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 39 publications
6
61
0
Order By: Relevance
“…This effect was robust, and the size of the implicit preference for different kinds of regularity was correlated with the perceptual fluency of these regularities, while there was some divergence between implicit and explicit preferences. Further Implicit Association Test experiments have shown that the symmetry is also associated with high arousal words and simple, easy mathematical equations [99]. The IAT certainly shows a form of implicit evaluation; however these studies are not evidence for automatic affective response to symmetry in the strongest sense.…”
Section: Question Six: Does Symmetry Processing Produce An Automatic mentioning
confidence: 90%
“…This effect was robust, and the size of the implicit preference for different kinds of regularity was correlated with the perceptual fluency of these regularities, while there was some divergence between implicit and explicit preferences. Further Implicit Association Test experiments have shown that the symmetry is also associated with high arousal words and simple, easy mathematical equations [99]. The IAT certainly shows a form of implicit evaluation; however these studies are not evidence for automatic affective response to symmetry in the strongest sense.…”
Section: Question Six: Does Symmetry Processing Produce An Automatic mentioning
confidence: 90%
“…and there may be various symmetrical axes but this does not make the property of "being symmetrical" qualitatively gradable. On the other hand, studies on aesthetic judgments of symmetry can assess and measure to what extent people appreciate a particular shape or configuration (e.g., [82][83][84][85]) and this goes to show that symmetrical patterns can be graded from a qualitative point of view based on the observer's assessment of pleasantness. The studies presented in this paper, however, take a different approach.…”
Section: Potential Impact and Limitations Of The Studymentioning
confidence: 99%
“…It's also common that recent fMRI studies in aesthetics focus on emotional contrasts of positive emotion to negative emotion (e.g. Bertamini, Makin and Rampone, 2013;Vessel et al, 2012). In addition, recent studies have found that emotional arousal is critical to aesthetic responses (Bertamini, Makin and Rampone, 2013;Okanoya, 2013) and suggested that emotional arousal should be included to account for aesthetic experience.…”
Section: Shared Neural Substrates Of Aesthetic Judgment and Emotionmentioning
confidence: 99%
“…Bertamini, Makin and Rampone, 2013;Vessel et al, 2012). In addition, recent studies have found that emotional arousal is critical to aesthetic responses (Bertamini, Makin and Rampone, 2013;Okanoya, 2013) and suggested that emotional arousal should be included to account for aesthetic experience. To get a better understanding of aesthetic emotions, we therefore included emotional arousal in the behavioral measures and investigated the contrasts between the positive, neutral, and negative emotion in the fMRI data.…”
Section: Shared Neural Substrates Of Aesthetic Judgment and Emotionmentioning
confidence: 99%